2015
DOI: 10.2174/1874120701509010075
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Solution-derived Hydroxyapatite Coatings on Titanium Alloy in the Presence of Magnetron-sputtered Alumina Bond Coats

Abstract: Hydroxyapatite Ca10(PO4)6(OH)2 (HAp) and calcium phosphate ceramic materials and coatings are widely used in medicine and dentistry because of their ability to enhance the tissue response to implant surfaces and promote bone ingrowth and osseoconduction processes. The deposition conditions have a great influence on the structure and biofunctionality of calcium phosphate coatings. Corrosion processes and poor adhesion to substrate material reduce the lifetime of implants with calcium phosphate coatings. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…This allows enhanced glenoid bone tissue response to the implant surface and promotes bone ingrowth and osseous conduction processes. 28 The mesh is designed with a pore size that more closely resembles host cancellous bone, allowing a press fit and mechanical interlock to develop through a greater friction coefficient. This also further reduces the degree of micro motion at this level, thereby reducing likelihood of radiolucencies.…”
Section: Discussionmentioning
confidence: 99%
“…This allows enhanced glenoid bone tissue response to the implant surface and promotes bone ingrowth and osseous conduction processes. 28 The mesh is designed with a pore size that more closely resembles host cancellous bone, allowing a press fit and mechanical interlock to develop through a greater friction coefficient. This also further reduces the degree of micro motion at this level, thereby reducing likelihood of radiolucencies.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent mechanical properties and chemical stability of alumina encourage to be used as coated material on a metallic implant surfaces. Alumina coatedTi6Al4V can improve corrosion resistance of material and biocompatibility (6,25) .…”
Section: Discussionmentioning
confidence: 99%
“…An aluminum oxide coating substrates showed improvement in corrosion resistance compared to uncoated titanium substrates (6) .Ceramic materials such as alumina, partially stabilized zirconia, and titania possess high wear resistance, mechanical strength, and good biocompatibility (7) . When preparing implant sockets, the infection or trauma to the alveolar bone appears to be one of the causative factor of early implant losses (8) , so researchers are increasingly focusing on the development of the antibacterial property of implants (9) .…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study showed that silver‐coated implants provided protection from bacterial growth and more angiogenesis could be observed compared with the control group (Shevtsov et al, ). Zykova et al acknowledged that HA coatings on Ti alloy in the presence of magnetron‐sputtered alumina bond coats exhibited higher corrosion resistance and better biocompatibility (Zykova et al, ).…”
Section: Surface Modification Techniquesmentioning
confidence: 99%
“…An in vitro study showed that silver-coated implants provided protection from bacterial growth and more angiogenesis could be observed compared with the control group(Shevtsov et al, 2019).Zykova et al acknowledged that HA coatings on Ti alloy in the presence of magnetron-sputtered alumina bond coats exhibited higher corrosion resistance and better biocompatibility(Zykova et al, 2015). The strong adhesion of the coatings to the surface is another prominent feature of this method.Shevtsov et al evaluated the effect of PVD silver coating on porous implants.…”
mentioning
confidence: 99%